Addressing concerns about smoking cessation and mental health: theoretical review and practical guide for healthcare professionals. (March 2021) - Taylor, Gemma M. J.; Baker, Amanda L.; Fox, Nadine; Kessler, David S.; Aveyard, Paul; Munafò, Marcus R.
SUMMARY: Smoking rates in people with depression and anxiety are twice as high as in the general population, even though people with depression and anxiety are motivated to stop smoking. Most healthcare professionals are aware that stopping smoking is one of the greatest changes that people can make to improve their health. However, smoking cessation can be a difficult topic to raise. Evidence suggests that smoking may cause some mental health problems, and that the tobacco withdrawal cycle partly contributes to worse mental health. By stopping smoking, a person's mental health may improve, and the size of this improvement might be equal to taking antidepressants. In this article we outline ways in which healthcare professionals can compassionately and respectfully raise the topic of smoking to encourage smoking cessation. We draw on evidence-based methods such as cognitive–behavioural therapy (CBT) and outline approaches that healthcare professionals can use to integrate these methods into routine care to help their patients stop smoking.